DEVELOPMENT OF STUDENT WORKSHEET (LKPD) BASED ON A SCIENTIFIC APPROACH ON COLLOID CONCEPT: MAKING CRACKERS FROM GREEN MUSSEL (PERNA VIRIDIS) SHELL - Dewi Murniati; Burhanudin Milama; Siti Aisah (JCER (Journal of Chemistry Education Research), 2023)
This study aims to develop LKPD based on a scientific approach to the colloid concept for the practice of making green mussel shell crackers. This type of research was conducted using the Four-D model which was adapted from Thiagarajan which consisted of four stages: define, design, development, and disseminate. However, this research is limited only to the development stage. The LKPD eligibility criteria developed were reviewed from several aspects, namely the feasibility aspect of the content, the presentation feasibility aspect, the language aspect, the graphic aspect, the teacher and student responses. The product has been validated and continued with a limited trial phase was carried out on 16 high school/MA chemistry teachers in the Jabodetabek area and 36 students in class XII science at SMAN 4 Tangerang City. Data were collected using a validation questionnaire which was prepared using the Guttman scale and the teacher and student response sheets were compiled using a Likert scale. The results of the limited trial through the teacher's response questionnaire to the LKPD developed were 86%; and the results of the student questionnaire of 83.5% which are included in the very good category and are suitable for use in learning the colloid concept.